GOD IN 'EARLY HINDI' BHAKTI : MALE AND FEMALE? - Callewaert, W. M. (Journal of Dharma, 1980)
In calculated contrast with the traditional Christian image of God as the bearded father, the first American astronauts replied to journalists who asked them whether they had seen God and how he looked : she is black. The image of a male God remains predominant in Christian culture for reasons which have their origin long before the beginning of the Christian era.' In the present article I examine the experience of God described by the bhakti poets of the 'Early Hindi' period. The term Early Hindi, although misleading is used for lack of a better one; it refers to the literature comprising both the sagun bhakti trends of the devotees of Krishna and of Ram and the nirgun bhakti reform movements of the Santas in North-India between the 12th and the 17th c. A.D.